TANGGUNG JAWAB SOSIAL BERDASARKAN ISO 26000 DAN NILAI PERUSAHAAN YANG LISTED DI BURSA EFEK INDONESIA - Latifah, Sri Wahjuni (Journal of Innovation in Business and Economics, 2012)
The research topic concern with corporate responsibility towards the environment related to the firm value. The objective of this research is to test compliance level of the public company in Indonesia against ISO 26000. The samples in this research are 36 companies which include LQ 45 that was chosen by using purposive sampling method. Techniques of data analysis were conducted by using the index that was analyzed with descriptive statistical techniques. The results of this study found that compliance levels are high (0.68). Similarly, seen from the value of the firm as measured by Tobin'q that the company has conducted environmental responsibility is also high (2.12).